Assessment of gingival thickness in primary, mixed and permanent dentition: part 3 - Shivani, Singh; Vandana, Kharidi Laxman (International Journal of Dental Research, 2017)
Aim and objective: The objective of this in-vivo study was to evaluate gingival thickness of mid buccally and interdentally in primary, mixed & permanent dentition.Method: The study included 40 subjects (22 males and 18 females) with 480 sites of an age range 4-25 Years. Subjects were divided into 3 groups – the primary dentition (4-6 years) mixed dentition (7-13 years) and adult dentition (16-25 years). All the parameters were measured in upper and lower anterior segments.Results: Gingival thickness (GT) was measured arch wise and tooth wise in different dentition and overall dentition wise without differentiating arch wise and toothwise. Gingival thickness (GT) was significantly higher (p=.001) in mixed dentition midbuccally (1.3 +0.46) and interdentally (2.31+0.71) in both the arches. GT (MB) was significantly higher in primary dentition (1.4+0.5) and GT (ID) was significant in mixed dentition (2.6+0.7).Conclusion: Gingival thickness increases from primary to mixed dentition and significantly higher in maxilla.